Next Generation Enterprise Architecture for SAP Cloud Systems Leveraging AI Driven Analytics and Hybrid Infrastructure (International Journal of Engineering & Extended Technologies Research (IJEETR), 2025)
The rapid evolution of cloud computing, artificial intelligence, and enterprise analytics has reshaped how organizations deploy, manage, and scale enterprise systems such as SAP. Modern enterprises require architectures that not only provide operational efficiency but also enable intelligent decision-making, data-driven insights, and agile digital transformation. This research explores the design and implementation of a next-generation AI-driven enterprise architecture for SAP cloud systems, integrating intelligent analytics, hybrid cloud infrastructure, and digital transformation strategies. The proposed framework leverages machine learning algorithms, real-time analytics, and hybrid infrastructure orchestration to optimize resource utilization, automate decision-making processes, and ensure robust system performance. By integrating AI into SAP cloud platforms, enterprises can achieve predictive insights, improved operational efficiency, and enhanced scalability across multi-cloud and on-premise environments. The research methodology combines architectural modeling, simulation experiments, and performance evaluation using enterprise datasets and SAP workloads. The results indicate that AI-driven architectures significantly improve system adaptability, predictive analytics accuracy, and hybrid infrastructure management, enabling organizations to accelerate digital transformation initiatives while maintaining high levels of security, resilience, and operational efficiency. The study provides a scalable, intelligent, and flexible enterprise architecture framework that addresses the challenges of modern SAP deployments and supports long-term organizational innovation.
Keywords: AI-driven architecture; SAP cloud systems; intelligent analytics; hybrid cloud infrastructure; enterprise digital transformation; machine learning; enterprise scalability; predictive insights; automated decision-making; cloud orchestration